Analysis of the Implementation of Merdeka Curriculum in Mathematics Learning Based on Jean Piaget's Cognitive Development Theory in Junior High School - Nadya Fitriani; Muhammad Zaini (Rangkiang Mathematics Journal, 2025)
This study aims to analyze the implementation of Merdeka Curriculum in mathematics learning in junior high schools based on Jean Piaget's cognitive development theory. The Merdeka Curriculum is designed to provide freedom for educators to arrange learning relevant to student needs, especially in mathematics subjects, which are often considered challenging. This research uses a qualitative approach with a case study type. The subject is a mathematics teacher. Data were obtained through document analysis and interviews, then analyzed descriptively through data reduction, data presentation, and conclusion drawing. To ensure data validity, source triangulation was carried out. The results showed that implementing the Merdeka Curriculum in mathematics learning supports students' formal operational cognitive development stage. The project-based approach and problem-solving at the core of the Merdeka Curriculum can develop logical, abstract, and analytical thinking skills essential in mathematics. However, several obstacles were found in the implementation, such as teachers‘ lack of understanding of learning strategies by students’ cognitive development stage, and limited interactive learning facilities. This research recommends comprehensive training for mathematics teachers to improve their ability to implement cognitive development-based learning strategies and the provision of adequate supporting facilities. With the right strategy, implementing the Merdeka Curriculum in mathematics learning in junior high schools can be more optimal in improving students' cognitive abilities.